Data compression: techniques and applications, hardware and software considerations - Held, Gilbert (Wiley ChichesterGB, 1991)
Examines new compression techniques including the Miccrocom Networking Protocol (MNP) and identifies various ways in which the efficiency of character- oriented and statistical-oriented compression techniques can be enhanced.